A Comparison of Midazolam Co-induction with Propofol Priming in Propofol Induced Anesthesia - Amatya, A; Marhatta, M N; Shrestha, G S; Shrestha, A; Amatya, A (Journal of Nepal Health Research Council, 2014)
Background: Combination therapy with two or more different drugs, with the intension of reaching the same therapeutic goal, was heavily criticized for a long time. However, it is accepted today, especially when advantage over monotherapy can be proved. Our study was undertaken to compare whether propofol priming and midazolam predosing would affect total induction dose requirement of Propofol. Methods: A prospective randomized, double blind control study was conducted where 120 patients (16-65 years) were divided into 3 groups. Group P received 0.4 mg/kg of Propofol, Group M received 0.05 mg/kg of Midazolam and Group N received 3ml of Normal Saline 5 minutes after intravenous pethidine 0.75 mg / kg given for analgesia. We compared the total dose of propofol requirement for induction of anaesthesia in all the 3 groups, taking loss of verbal contact as the end point. Additionally, changes in haemodynamic status like blood pressure and heart rate at various intervals were studied and compared among the groups. Results: The groups were similar in terms of age, sex, weight and American Society of Anesesthesiologists Physical Status.The dose of Propofol required to induce anesthesia in Midazolam group was 1.58 mg/kg,1.86mg/kg in Propofol group and 1.96mg/kg in the control group. There were less hemodynamic changes in Midazolam group compared to the other two. Conclusions: Pre-dosing with Midazolam is more effective than Propofol priming in reducing the dose of Propofol induced anaesthesia associated with minimum hemodynamic alterations. Keywords: Co Induction, Priming, Propofol.